Molecularly imprinted membrane for transport of urea, creatinine, and vitamin B12 as a hemodialysis candidate membrane - Djunaidi Muhammad Cholid (De Gruyter, 2021)
High levels of urea and creatinine in the blood are a sign of decreased kidney function. To remove these substances from the blood, hemodialysis which utilizes membranes could be used. In this study, a molecularly imprinted membrane (MIM) was synthesized for the selective transport of urea. The synthesis is initiated with the polymerization of eugenol into polyeugenol and then into polyeugenoxy acetate (PA). The PA is then contacted with urea and then used as the functional polymer in the synthesis of MIM with polysulfone as the membrane base, and polyethylene glycol as the cross-linking agent. The result was later analyzed with FTIR and SEM-EDX. The membrane is then used in the transport of urea, creatinine, and vitamin B12 and then compared with the non-imprinted membrane (NIM) performance. By using UV-Vis spectrophotometry, the results showed that the membrane with 10 h heating variation is able to transport more urea and is more selective than NIM; this proves that the urea template on the MIM enables it to recognize urea molecules better than creatinine and vitamin B12. The order of transport from the best results is urea > creatinine > vitamin B12.